2017
DOI: 10.31235/osf.io/jk3n4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Swing Voting in the 2016 Presidential Election in Counties Where Midlife Mortality has been Rising in White Non-Hispanic Americans

Abstract: Understanding the effects of widespread disruption of the social fabric on public health outcomes can provide insight into the forces that drive major political realignment. Our objective was to estimate the association between increases in mortality in middle-aged non-Hispanic white adults from 1999-2005 to 2009-2015, health inequalities in life expectancy by income, and the surge in support for the Republican Party in pivotal US counties in the 2016 presidential election. We conducted a longitudinal ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 5 publications
2
9
0
1
Order By: Relevance
“…Similarly, related determinants of 2016 voting were increased mortality at the county level (Bilal et al . 2018), increased import competition from China (Autor et al . 2016), status threat (Mutz 2018), fear of terrorism (MacWilliams 2016), neighbourhood exposure to racial and ethnic minorities (Knowles and Tropp 2018), belief in the legitimacy of the economic system, and gender relations in society (Azevedo et al .…”
Section: Relevant Literaturementioning
confidence: 99%
“…Similarly, related determinants of 2016 voting were increased mortality at the county level (Bilal et al . 2018), increased import competition from China (Autor et al . 2016), status threat (Mutz 2018), fear of terrorism (MacWilliams 2016), neighbourhood exposure to racial and ethnic minorities (Knowles and Tropp 2018), belief in the legitimacy of the economic system, and gender relations in society (Azevedo et al .…”
Section: Relevant Literaturementioning
confidence: 99%
“…Compared to prior elections, the 2016 U.S. Presidential election witnessed a shift of votes toward the Republican candidate in communities that have experienced recent stagnation or decline in life expectancy. 4,5 A recent analysis examined the association between community health and the shift from 2016 to 2018 in Republican share of the vote in U.S. House of Representatives elections. 10 Although there was a general shift toward Democratic candidates in the 2018 election, we found that voting in less healthy communities continued to favor Republican candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have described the association between changes in life expectancy and voting behavior, noting a shift toward the Republican presidential candidate in counties where life expectancy has declined or increased the least. 3-5 One analysis found a 9.1 percentage point increase in the Republican vote share from 2008 to 2016 in counties in which life expectancy stagnated or declined from 1980 to 2014. 4 Voters in those counties were more likely to vote for Republican candidates in 2016, irrespective of prior voting patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Visto esto, la situación en salud y la victoria de Trump no están desconectadas. En otro artículo que publicamos en 2018 mostramos como las zonas donde más había aumentado la mortalidad en los años previos a las elecciones, y las zonas con mayores desigualdades en salud, habían sido las zonas que más habían aumentado la proporción de voto hacia Trump, con respecto a elecciones anteriores 6 . En esta situación de gobierno en retirada, mensajes de odio y empeoramiento de la salud de la población, llega el COVID-19.…”
Section: Figura 1 Esperanza De Vida Al Nacer En Ambos Sexos En Eeuu unclassified